Evaluación de aprendizajes por competencias de modo virtual en estudiantes de educación inicial de la facultad de ciencias de la educación y humanidades Universidad Nacional de la Amazonía Peruana, Iquitos 2021 - Varas Rengifo, Carolina Yesenia (2022)
The general objective of the research was to describe the evaluation of learning by competencies in a virtual way in initial education students of the Faculty of Educational Sciences and Humanities at the National University of the Peruvian Amazon in Iquitos in 2021. The methodology was quantitative, non-experimental, descriptive type with cross-sectional, field, and univariate design. The study population was 92 initial education students, who also made up the sample. The data collection was done through the survey technique and with a questionnaire which was validated by expert teachers. It is concluded that the evaluation of learning by competencies in virtual mode used by initial education students of the Faculty of Educational Sciences and Humanities at the National University of the Peruvian Amazon is adequate in 23.9%; in 75.0% little adequate and in 1.1% inadequate.